Experiential Education and Adolescents$1 (BPersonal and Spiritual Developments A Mixed-Method Study in the Secondary School Context of Hong Kong - Cheung, Chung Kwan Ackie; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2013)
Adventure-based programs have become prevailing in the schools in Hong Kong. Due to the little empirical examination to the frequent use of experiential education, Chung Kwan Ackie Cheung uses mixed methods to establish its first phenomenal picture, addressing the scale of the use of experiential education and the impact of it on adolescents$1 (Bdevelopment with regard to the globalizing phenomenon of Hong Kong. The findings show that experiential education, esp. adventure-based program, has been widely-spread and there is positive impact in the specified aspects self-concept, self-efficacy, learning climate and spiritual dimension of its adolescent learners.s
Keywords: Education; Education; International and Comparative Education; Education (general).